George S. Kaufman papers - Kaufman, George S. (George Simon), 1889-1961.
Typescripts of plays by Kaufman. Includes the comedies "June Moon," "Dinner at Eight," and "Stage Door" along with the musical comedies "The Cocoanuts," "Helen of Troy, New York," and "Let 'Em Eat Cake." Coauthors include Marc Connelly, W. W. de Renne, Edna Ferber, Moss Hart, Ring Lardner, Isabel Leighton, Herman J. Mankiewicz, Robert Nathan, Irving Pichel, Morrie Ryskind, Herbert Seligman, and Alexander Woollcott.
Playwright and newspaperman.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Connelly, Marc, -- 1890-1980.; De Renne, W. W; Ferber, Edna, -- 1887-1968.; Hart, Moss, -- 1904-1961.; Lardner, Ring, -- 1885-1933.; Leighton, Isabel; Mankiewicz, Herman J. -- 1897-1953.; Nathan, Robert, -- 1894-1985.; Pichel, Irving, -- 1891-1954.; Ryskind, Morrie, -- 1895-1985.; Seligman, Herbert; Woollcott, Alexander, -- 1887-1943.; American drama (Comedy); Drama -- Stories, plots, etc; Musicals; Newspapermen; Playwrights